In vivo characterisation of a therapeutically relevant self‐assembling 18F‐labelled β‐sheet forming peptide and its hydrogel using positron emission tomography. (4th August 2017) - Morris, O.; Elsawy, M.A.; Fairclough, M.; Williams, K.J.; Mcmahon, A.; Grigg, J.; Forster, D.; Miller, A.F.; Saiani, A.; Prenant, C.
Abstract : Positron emission tomography (PET) and fluorescence labelling have been used to assess the pharmacokinetics, biodistribution and eventual fate of a hydrogel‐forming nonapeptide, FEFKFEFKK (F9), in healthy mice, using 18 F‐labelled and fluorescein isothiocyanate (FITC)‐labelled F9 analogues. F9 was site‐specifically radiolabelled with 2‐[ 18 F]fluoro‐3‐pyridinecarboxaldehyde ([ 18 F]FPCA) via oxime bond formation. [ 18 F]FPCA‐F9 in vivo fate was evaluated both as a solution, following intravenous administration, and as a hydrogel when subcutaneously injected. The behaviour of FITC‐F9 hydrogel was assessed following subcutaneous injection. [ 18 F]FPCA‐F9 demonstrated high plasma stability and primarily renal excretion; [ 18 F]FPCA‐F9 when in solution and injected into the bloodstream displayed prompt bladder uptake (53.4 ± 16.6 SUV at 20 minutes postinjection) and rapid renal excretion, whereas [ 18 F]FPCA‐F9 hydrogel, formed by co‐assembly of [ 18 F]FPCA‐F9 monomer with unfunctionalised F9 peptide and injected subcutaneously, showed gradual bladder accumulation of hydrogel fragments (3.8 ± 0.4 SUV at 20 minutes postinjection), resulting in slower renal excretion. Gradual disaggregation of the F9 hydrogel from the site of injection was monitored using FITC‐F9 hydrogel in healthy mice (60 ± 3 over 96 hours), indicating a biological half‐life between 1 and 4 days. The in vivo characterisation of F9, both as a gel and a solution, highlights its potential as a biomaterial. Abstract : Positron emission tomography (PET) and fluorescence labelling have been used to assess the pharmacokinetics, biodistribution and eventual fate of a hydrogel‐forming nonapeptide: FEFKFEFKK (F9). The results have confirmed that the in vivo behaviour of labelled F9 is typical of natural small peptides, which was not altered on account of gelation. Labelled F9 exhibited renal excretion, high plasma stability and a favourable biological half‐life and thus has potential as a biomaterial.